A Characterization of Clouds and Precipitation Over the Southern Ocean From Synoptic to Micro Scales During the CAPRICORN Field Campaigns. Issue 17 (12th September 2022) - Montoya Duque, E.; Huang, Y.; Siems, S. T.; May, P. T.; Protat, A.; McFarquhar, G. M.
Abstract: The persistent Southern Ocean (SO) shortwave radiation biases in climate models and reanalyses have been associated with the poor representation of clouds, precipitation, aerosols, the atmospheric boundary layer, and their intrinsic interactions. Capitalizing on shipborne observations collected during the Clouds Aerosols Precipitation Radiation and atmospheric Composition Over the Southern Ocean 2016 and 2018 field campaigns, this research investigates and characterizes cloud and precipitation processes from synoptic to micro scales. Distinct cloud and precipitation regimes are found to correspond to the seven thermodynamic clusters established using a K‐means clustering technique, while less distinctions are evident using the cyclone and (cold) front compositing methods. Cloud radar and disdrometer data reveal that light precipitation is common over the SO with higher intensities associated with cyclonic and warm frontal regions. Multiple lines of evidence suggest the presence of diverse microphysical features in several cloud regimes, including the likely dominance of ice aggregation in deep precipitating clouds. Signatures of mixed phase, and in some cases, riming were detected in shallow convective clouds away from the frontal conditions. Two of the K‐means clusters with contrasting cloud and precipitation properties are observed over the high‐latitude SO and coastal Antarctica, suggesting distinct physical processes therein. Through a single case study, in‐situ and remote‐sensing data collected by an overflight of the Southern Ocean Clouds Radiation Aerosol Transport Experimental Study were also evaluated and complement the ship‐based analysis. Plain Language Summary: The current generation of climate models and reanalyses products have difficulties in properly representing the radiative balance over the Southern Ocean (SO), which can be traced to the poor understanding of clouds and precipitation processes in this region. The remote location of the SO is a key factor for the lack of field observations that allow the scientific community to address the above‐mentioned problem. However, recent coordinated field campaigns have collected an unprecedented amount of data, offering new opportunities to explore this understudied region. This research paper aims to study clouds and precipitation processes over the SO using shipborne data collected from two field campaigns in 2016 and 2018. Using different synoptic classification techniques, we identify unique macro and micro cloud and precipitation behaviors that correspond to the various weather patterns across a wide range of latitudes. In addition, we use aircraft observations collected from an overflight to evaluate and complement our analysis of the shipborne data. The study offers a framework that may help better understand the nature of the model biases over the SO. Key Points: Distinct cloud and precipitation regimes correspond to the Southern Ocean synoptics, defined using a sounding K‐means clustering technique Evidence suggests diverse microphysical features, like mixed phase in shallow convection and ice aggregation in deep precipitating clouds Two unique synoptic patterns have unique cloud and precipitation properties over the high‐latitudes, where climate models have large biases